Stopovers and Connecting Flights. A discussion of Where is American Literature? by Caroline F. Levander - Buchholtz, Mirosława (Theoria et Historia Scientiarum, 2016)
The face of American literature is changing in the era of digital technologies. This fact has been recognized by different generations of American scholars defining the scene today. For example, both J. Hillis Miller and Caroline F. Levander admit that the traditional understanding of literature as a selection of venerated texts is over as the internet both opens up new vistas and poses new challenges to the studying and teaching of literature, and especially national literature. It is time again to pose simple questions in an attempt to redefine the current discourse in literary research. Levander’s book, read at the background of past and recent scholarship, serves as a starting point for discussions concerning American literature viewed as a dynamic field of collaborative production.